USING SIMULINK PACKAGE FOR TRANSIENT SUPPORT-PARAMETRIC SIMULATION IN GAS PIPELINE SECTION - Nikita V. Kudinov; Rudolf A. Neydorf; Lev А. Zhuravlev; Elena V. Teterevleva (Advanced Engineering Research, 2012)
The possibilities of the modern software package of block - modular simulation to the transient simulation tasks in the gas stream in the natural gas transportation area are considered. An approach to modeling in vec tor format the spatiall y distributed cell model object generated on the special nonlinear basis is offered. This permits to solve the problems on diagnosis and flow control in the transient processes by macro - cellular modeling of its mass and kinetic energy balance. The adequacy of the starting and ending state of the cell model is provided by the calculation of the reference - parameter vector that characterizes the steady - state flow, and by comparing it with these states.